Art at the turn of the millennium - Bang Larsen, Lars; Riemschneider, Burkhard; Grosenick, Uta; Blase, Christopher; Dziewior, Yilmaz; Ribettes, Jean-Michel; Stange, Raimer; Titz, Susanne; Verwoert, Jan; Wege, Astrid (Köln : Taschen, 1999)
The art of the 1980s and 90s can seem like an impenetrable tangle of -isms that are alarmingly diverse and mutually contradictory in the post-postmodern age, anything and everything goes. The new generation of artists has a penchant for venturing into territory not traditionally associated with high art, and designers, architects, and film-makers can be found of the cutting edge. This book offers a broad overview of the international art scene at the end of the twentieth century. Four pages are devoted to each of the 137 artists featured, all of whom are listed alphabetically. Their work is introduced with pithy commentaries and displayed in more than 1200 illustrations, documenting the latest trends in art. As the millenium draws to a close, this guide suggests directions in which the art of the future might be heading.
Absalon ; Ackermann, Franz ; Ahtila, Eija-Liisa ; Althoff, Kai ; Antoni, Janine ; Araki, Nobuyoshi ; Armleder, John M. ; Art Club 2000 ; Baechler, Donald ; Balka, Miroslaw ; Balkenhol, Stephan ; Barney, Matthew ; Basquiat, Jean-Michel ; Beecroft, Vanessa ; Bickerton, Ashley ; Bleckner, Ross ; Bonin, Cosima von ; Bulloch, Angela ; Bustamante, Jean-Marc ; Calle, Sophie ; Cattelan, Maurizio ; Chapman, Dinos & Jake ; Clark, Larry ; Clegg & Guttmann ; Currin, John ; Delvoye, Wim ; Demand, Thomas ; Dijkstra, Rineke ; Dion, Mark ; Douglas, Stan ; Dumas, Marlene ; Edmier, Keith ; Eliasson, Olafur ; Emin, Tracey ; Fischli, Peter ; Weiss, David ; Fleury, Sylvie ; Förg, Gunther ; Fritsch, Katharina ; General Idea ; Genzken, Isa ; Gillick, Liam ; Gober, Robert ; Goldin, Nan ; Gonzalez-Torres, Felix ; Gordon, Douglas ; Green, Renée ; Group Material ; Grünfeld, Thomas ; Gursky, Andreas ; Halley, Peter ; Hatoum, Mona ; Herold, Georg ; Hill, Gary ; Hirst, Damien ; Höfer, Candida ; Höller, Carsten ; Holzer, Jenny ; Honert, Martin ; Horn, Roni ; Hume, Gary ; Huyghe, Pierre ; Hyber, Fabrice ; Kabakov, Ilya ; Kelley, Mike ; Kippenberger, Martin ; Knowbotic Research ; Koester, Joachim ; Koons, Jeff ; Kruger, Barbara ; Land, Peter ; Landers, Sean ; Lawler, Louise ; Leonard, Zoe ; Levine, Sherrie ; Atelier van Lieshout ; Locher, Thomas ; Lockhart, Sharon ; Lucas, Sarah ; Majerus, Michel ; McCarthy, Paul ; McCollum, Allan ; Merz, Gerhard ; Moffatt, Tracey ; Mori, Mariko ; Mullican, Matt ; Noland, Cady ; Oehlen, Albert ; Orozco, Gabriel ; Oursler, Tony ; Pardo, Jorge ; Parreno, Philippe ; Pernice, Manfred ; Peterman, Dan ; Pettibon, Raymond ; Peyton, Elizabeth ; Pierson, Jack ; Pippin, Steven ; Prina, Stephen ; Prince, Richard ; Ray, Charles ; Rehberger, Tobias ; Rhoades, Jason ; etc.
Engelse en Nederlandse tekst
boek